Photovoltaic impact-resistant frit and preparation method thereof

By using a combination of materials such as calcium carbonate to prepare impact-resistant fuses for photovoltaics, the problem of insufficient impact resistance of existing photovoltaic panel fuses is solved, significantly improving the impact resistance and stability of photovoltaic panels and extending the service life.

CN119263637APending Publication Date: 2025-01-07JIANGSU BAIFU TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411167430.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The fuses on existing photovoltaic panels are easily damaged by impact when used, which cannot improve the impact resistance, resulting in damage to the photovoltaic panels, affecting the normal use of users and the protection of equipment.

Method used

Using the combination of calcium carbonate, quartz, zircon sand, borax, lead dan, polycarbonate, polystyrene, polyethylene, polypropylene and PVB film raw materials, the impact-resistant frit is prepared by crushing, grinding, mixing and baking steps. , increase the impact strength and stability of the frit.

Benefits of technology

It effectively improves the impact resistance of photovoltaic panels, prevents fuses and photovoltaic panels from being damaged by impact, extends service life, reduces the need to replace photovoltaic panels, and achieves all-round protection.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a photovoltaic impact-resistant frit and a preparation method thereof. The photovoltaic impact-resistant frit is prepared from the following components in parts by weight: 25-35 parts of carbonic acid, 25-30 parts of quartz, 10-20 parts of zircon sand, 6-8 parts of borax, 10-20 parts of minium, 10-15 parts of potassium nitrate, 15-25 parts of polycarbonate, 6-10 parts of polystyrene, 3-5 parts of polyethylene, 4-6 parts of polypropylene and 7-9 parts of PVB (Polyvinyl Butyral) film raw materials. Through cooperation of quartz, zircon sand, borax and minium, the raw materials can be punched to form a transparent frit, through arrangement of polycarbonate, polystyrene, polyethylene and polypropylene, the impact strength of the frit can be improved, through arrangement of heel carbonate, potassium nitrate and a PVB film, the raw materials can be tightly mixed together, and the impact strength of the frit is improved. When a user uses the photovoltaic frit, the photovoltaic frit cannot be impacted and damaged, the photovoltaic panel cannot be damaged, and the impact resistance effect can be improved, so that it is ensured that the photovoltaic frit is not prone to being damaged when the user normally uses the photovoltaic frit, the photovoltaic panel can be protected in an all-around mode, and the user does not need to replace the photovoltaic panel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaics, in particular to an impact-resistant frit for photovoltaics and a preparation method thereof. Background Art

[0002] Photovoltaic, or photovoltaic power generation system, is a power generation system that uses the photovoltaic effect of semiconductor materials to convert solar radiation energy into electrical energy. The energy of the photovoltaic power generation system comes from inexhaustible solar energy, which is a clean, safe and renewable energy source. The photovoltaic power generation process does not pollute the environment or damage the ecology. Photovoltaic power generation systems are divided into independent photovoltaic systems and grid-connected photovoltaic systems. Photovoltaic power generation systems are composed of solar cell arrays, battery packs, charge and discharge controllers, inverters, AC distribution cabinets, solar tracking control systems and other equipment.

[0003] Photovoltaic panels are needed for collecting photovoltaics, and frits are needed on the surface of photovoltaic panels. For example, a Chinese patent discloses a matte frit for architectural ceramics and a preparation method thereof. The patent number is: CN102557739A, which belongs to the field of ceramic production technology. The weight parts of each component are 25-35 parts of quartz, 25-30 parts of calcite, 10-20 parts of lithium feldspar, 5-8 parts of zinc oxide, 3-8 parts of boric acid, 5-10 parts of zircon powder, 2-5 parts of raw talc and 1-3 parts of strontium carbonate. The preparation method is as follows: the above raw materials are then stirred and mixed evenly, and placed in a frit furnace to melt. The melting temperature is 1400-1500°C, and the melting time is 6-8 hours, and quench the melted liquid with cold water; the matte frit prepared by the method feels like jade, is delicate and smooth, has good stability, and has a relatively wide firing range. The ceramic tiles made of the frit are used for decoration, giving people a sense of elegance and a visual enjoyment. The value of the ceramic tiles is improved, and the added value is greatly improved. The patent is delicate and smooth when used, has good stability, and has a relatively wide firing range, but it cannot resist impact, resulting in the photovoltaic frit being easily damaged by impact when used by the user, and the photovoltaic panel is easily damaged, and the impact resistance effect cannot be improved, thereby affecting the normal use of the user. It is easy to be damaged, and the photovoltaic panel cannot be protected in all directions, and the user needs to replace the photovoltaic panel. Summary of the invention

[0004] In order to solve the problems raised in the above background technology, the purpose of the present invention is to provide an impact-resistant frit for photovoltaics and a preparation method thereof, which has the advantage of improving the impact resistance effect and solves the problem that the frit cannot improve the impact resistance effect.

[0005] To achieve the above object, the present invention provides the following technical solution: an impact-resistant frit for photovoltaics, wherein the weight proportions of the components are:

[0006] 25-35 parts of carbonate, 25-30 parts of quartz, 10-20 parts of zircon sand, 6-8 parts of borax, 10-20 parts of red lead, 10-15 parts of potassium nitrate, 15-25 parts of polycarbonate, 6-10 parts of polystyrene, 3-5 parts of polyethylene, 4-6 parts of polypropylene and 7-9 parts of PVB film raw materials.

[0007] As a preferred embodiment of the present invention, the quartz is quartz powder, the zircon sand is zircon sand powder, and the borax is borax powder.

[0008] As the present invention is preferred, comprising the following steps:

[0009] Crushing step: pouring quartz, zircon sand, borax and red lead into the interior of the crushing device, crushing the quartz, zircon sand, borax and red lead by the crushing device, the crushing time is: 10-20 minutes, after completion, pouring polycarbonate, polystyrene, polyethylene and polypropylene into the interior of the crushing device for crushing, the crushing time is: 20-40 minutes;

[0010] Grinding step: pouring the crushed quartz, zircon sand, borax and red lead into the interior of a grinding device, grinding the quartz, zircon sand, borax and red lead by the grinding device for 20-40 minutes, so that the quartz, zircon sand, borax and red lead form relatively fine powders, and then pouring the crushed polycarbonate, polystyrene, polyethylene and polypropylene into the interior of the grinding device for grinding for 20-30 minutes, so that the polycarbonate, polystyrene, polyethylene and polypropylene form powders;

[0011] Mixing steps: the user first pours quartz, zircon sand, borax and red lead powder into the mixer for mixing for 15-25 minutes to form mixture one, then pours polycarbonate, polystyrene, polyethylene and polypropylene into the mixer for mixing with mixture one for 25-35 minutes to form mixture two, then pours helium carbonate, potassium nitrate and PVB film raw materials into the mixer for mixing with mixture two for 1-2 hours to form mixture three;

[0012] Baking steps: the user puts mixture three into the oven and bakes the mixture three in the oven at a baking temperature of 1090-1120°C for 5-7h, and then cools the mixture to form a semi-finished melt. After baking, the semi-finished melt is put into the oven again at a baking temperature of 720-780°C for 4-5h. After completion, the mixture is water quenched to form a melt.

[0013] As a preferred embodiment of the present invention, in the pulverizing step, an observation glass is provided inside the pulverizing device, and the raw materials processed inside the pulverizing device can be observed through the transparent observation glass, thereby ensuring the processing effect of the raw materials.

[0014] As a preferred embodiment of the present invention, in the grinding step: a cover plate is provided on the top of the grinding device, and by providing the cover plate, the top of the grinding device can be sealed to prevent dust generated by the grinding device from floating out.

[0015] As a preferred embodiment of the present invention, in the mixing step, a pouring device is provided on the top of the mixer, and the raw materials are introduced into the interior of the mixer through the pouring device.

[0016] As a preferred embodiment of the present invention, in the baking step, the feed port of the oven is movably connected to an oven door via a hinge, and by providing the oven door, the oven opening can be sealed to prevent leakage from occurring at the oven opening.

[0017] As a preferred embodiment of the present invention, in the baking step: a handle is fixedly connected to a side of the oven door away from the oven, and the handle is provided to facilitate the user to open the oven door.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The present invention can form a transparent frit by combining quartz, zircon sand, borax and red lead. The impact resistance of the frit can be increased by arranging polycarbonate, polystyrene, polyethylene and polypropylene. The raw materials can be closely mixed by arranging helium carbonate, potassium nitrate and PVB film. When the user uses it, the photovoltaic frit will not be damaged by impact, and the photovoltaic panel will not be damaged. The impact resistance effect can be improved, thereby ensuring that the user's normal use is not easy to be damaged, and the photovoltaic panel can be protected in all directions, and the user does not need to replace the photovoltaic panel. DETAILED DESCRIPTION

[0020] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Embodiment 1

[0022] The invention discloses an impact-resistant frit for photovoltaic use. The weight proportions of the components are as follows: 25 parts of carbonate, 25 parts of quartz, 10 parts of zircon sand, 6 parts of borax, 10 parts of red lead, 10 parts of potassium nitrate, 15 parts of polycarbonate, 6 parts of polystyrene, 3 parts of polyethylene, 4 parts of polypropylene and 7 parts of PVB film raw materials.

[0023] A method for preparing an impact-resistant frit for photovoltaics comprises the following steps:

[0024] Crushing step: pouring quartz, zircon sand, borax and red lead into the crushing device, crushing the quartz, zircon sand, borax and red lead by the crushing device, the crushing time is: 10 minutes, after completion, pouring polycarbonate, polystyrene, polyethylene and polypropylene into the crushing device for crushing, the crushing time is: 20 minutes;

[0025] Grinding step: pouring the crushed quartz, zircon sand, borax and red lead into the interior of a grinding device, grinding the quartz, zircon sand, borax and red lead by the grinding device for 20 minutes, so that the quartz, zircon sand, borax and red lead form relatively fine powders, and then pouring the crushed polycarbonate, polystyrene, polyethylene and polypropylene into the interior of the grinding device for grinding for 20 minutes, so that the polycarbonate, polystyrene, polyethylene and polypropylene form powders;

[0026] Mixing steps: the user first pours quartz, zircon sand, borax and red lead powder into the mixer for mixing for 15 minutes to form mixture 1, then pours polycarbonate, polystyrene, polyethylene and polypropylene into the mixer for mixing with mixture 1 for 25 minutes to form mixture 2, then pours helium carbonate, potassium nitrate and PVB film raw materials into the mixer for mixing with mixture 2 for 1 hour to form mixture 3;

[0027] Baking steps: the user puts mixture three into the oven and bakes the mixture three in the oven at a baking temperature of 1090°C for 5 hours, then cools the mixture to form a semi-finished melt. After baking, the semi-finished melt is put into the oven again at a baking temperature of 720°C for 4 hours, and then water quenched to form a melt.

[0028] Embodiment 2

[0029] A photovoltaic impact-resistant frit comprises the following components in parts by weight: 30 parts of carbonate, 28 parts of quartz, 15 parts of zircon sand, 7 parts of borax, 15 parts of red lead, 13 parts of potassium nitrate, 18 parts of polycarbonate, 8 parts of polystyrene, 4 parts of polyethylene, 5 parts of polypropylene and 8 parts of PVB film raw material.

[0030] A method for preparing an impact-resistant frit for photovoltaics comprises the following steps:

[0031] Crushing step: pouring quartz, zircon sand, borax and red lead into the interior of the crushing device, crushing the quartz, zircon sand, borax and red lead by the crushing device, the crushing time is: 15 minutes, after completion, pouring polycarbonate, polystyrene, polyethylene and polypropylene into the interior of the crushing device for crushing, the crushing time is: 30 minutes;

[0032] Grinding step: pouring the crushed quartz, zircon sand, borax and red lead into the interior of a grinding device, grinding the quartz, zircon sand, borax and red lead by the grinding device for 30 minutes, so that the quartz, zircon sand, borax and red lead form relatively fine powders, and then pouring the crushed polycarbonate, polystyrene, polyethylene and polypropylene into the interior of the grinding device for grinding for 25 minutes, so that the polycarbonate, polystyrene, polyethylene and polypropylene form powders;

[0033] Mixing steps: the user first pours quartz, zircon sand, borax and red lead powder into the mixer for mixing for 18 minutes to form mixture 1, then pours polycarbonate, polystyrene, polyethylene and polypropylene into the mixer for mixing with mixture 1 for 30 minutes to form mixture 2, then pours helium carbonate, potassium nitrate and PVB film raw materials into the mixer for mixing with mixture 2 for 1 hour and 30 minutes to form mixture 3;

[0034] Baking steps: the user puts mixture three into the oven and bakes the mixture three in the oven at a baking temperature of 1110°C for 6 hours, then cools the mixture to form a semi-finished melt. After baking, the semi-finished melt is put into the oven again at a baking temperature of 750°C for 4 hours and 30 minutes. After completion, the mixture is water quenched to form a melt.

[0035] Embodiment 2

[0036] A photovoltaic impact-resistant frit comprises the following components in parts by weight: 35 parts of sodium carbonate, 30 parts of quartz, 20 parts of zircon sand, 8 parts of borax, 20 parts of red lead, 15 parts of potassium nitrate, 25 parts of polycarbonate, 10 parts of polystyrene, 5 parts of polyethylene, 6 parts of polypropylene and 9 parts of PVB film raw materials.

[0037] A method for preparing an impact-resistant frit for photovoltaics comprises the following steps:

[0038] Crushing step: pouring quartz, zircon sand, borax and red lead into the crushing device, crushing the quartz, zircon sand, borax and red lead by the crushing device, the crushing time is: 20 minutes, after completion, pouring polycarbonate, polystyrene, polyethylene and polypropylene into the crushing device for crushing, the crushing time is: 40 minutes;

[0039] Grinding step: pouring the crushed quartz, zircon sand, borax and red lead into the interior of a grinding device, grinding the quartz, zircon sand, borax and red lead by the grinding device for 40 minutes, so that the quartz, zircon sand, borax and red lead form relatively fine powders, and then pouring the crushed polycarbonate, polystyrene, polyethylene and polypropylene into the interior of the grinding device for grinding for 30 minutes, so that the polycarbonate, polystyrene, polyethylene and polypropylene form powders;

[0040] Mixing steps: the user first pours quartz, zircon sand, borax and red lead powder into the mixer for mixing for 25 minutes to form mixture 1, then pours polycarbonate, polystyrene, polyethylene and polypropylene into the mixer for mixing with mixture 1 for 35 minutes to form mixture 2, then pours helium carbonate, potassium nitrate and PVB film raw materials into the mixer for mixing with mixture 2 for 2 hours to form mixture 3;

[0041] Baking steps: the user puts mixture three into the oven and bakes the mixture three in the oven at a baking temperature of 1120°C for 7 hours, then cools the mixture to form a semi-finished melt. After baking, the semi-finished melt is put into the oven again at a baking temperature of 780°C for 5 hours, and then water quenched to form a melt.

[0042] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0043] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A photovoltaic impact-resistant frit, characterized in that: The weight parts of each component are: 25-35 parts of carbonate, 25-30 parts of quartz, 10-20 parts of zircon sand, 6-8 parts of borax, 10-20 parts of red lead, 10-15 parts of potassium nitrate, 15-25 parts of polycarbonate, 6-10 parts of polystyrene, 3-5 parts of polyethylene, 4-6 parts of polypropylene and 7-9 parts of PVB film raw materials.

2. The photovoltaic impact-resistant frit according to claim 1, characterized in that: The quartz is quartz powder, the zircon sand is zircon sand powder, and the borax is borax powder.

3. The method for preparing a photovoltaic impact-resistant frit according to claim 2, characterized in that: The following steps are involved: Crushing step: pouring quartz, zircon sand, borax and red lead into the interior of the crushing device, crushing the quartz, zircon sand, borax and red lead by the crushing device, the crushing time is: 10-20 minutes, after completion, pouring polycarbonate, polystyrene, polyethylene and polypropylene into the interior of the crushing device for crushing, the crushing time is: 20-40 minutes; Grinding step: pouring the crushed quartz, zircon sand, borax and red lead into the interior of a grinding device, grinding the quartz, zircon sand, borax and red lead by the grinding device for 20-40 minutes, so that the quartz, zircon sand, borax and red lead form relatively fine powders, and then pouring the crushed polycarbonate, polystyrene, polyethylene and polypropylene into the interior of the grinding device for grinding for 20-30 minutes, so that the polycarbonate, polystyrene, polyethylene and polypropylene form powders; Mixing steps: the user first pours quartz, zircon sand, borax and red lead powder into the mixer for mixing for 15-25 minutes to form mixture one, then pours polycarbonate, polystyrene, polyethylene and polypropylene into the mixer for mixing with mixture one for 25-35 minutes to form mixture two, then pours helium carbonate, potassium nitrate and PVB film raw materials into the mixer for mixing with mixture two for 1-2 hours to form mixture three; Baking steps: the user puts mixture three into the oven and bakes the mixture three in the oven at a baking temperature of 1090-1120°C for 5-7h, and then cools the mixture to form a semi-finished melt. After baking, the semi-finished melt is put into the oven again at a baking temperature of 720-780°C for 4-5h. After completion, the mixture is water quenched to form a melt.

4. The method for preparing a photovoltaic impact-resistant frit according to claim 3, characterized in that: The crushing step: an observation glass is provided inside the crushing device, and the raw materials processed inside the crushing device can be observed through the transparent observation glass, thereby ensuring the processing effect of the raw materials.

5. The method for preparing a photovoltaic impact-resistant frit according to claim 4, characterized in that: The grinding step: a cover plate is arranged on the top of the grinding device, and the cover plate can be arranged to seal the top of the grinding device to prevent dust generated by the grinding device from floating out.

6. The method for preparing a photovoltaic impact-resistant frit according to claim 5, characterized in that: The mixing step: a pouring device is arranged on the top of the mixer, and the raw materials are introduced into the interior of the mixer through the pouring device.

7. The method for preparing an impact-resistant frit for photovoltaic use according to claim 6, characterized in that: The baking step: the feed port of the oven is movably connected with an oven door via a hinge, and the oven door can be provided to seal the oven opening to prevent leakage.

8. The method for preparing an impact-resistant frit for photovoltaic use according to claim 7, characterized in that: The baking step: a handle is fixedly connected to a side of the oven door away from the oven, and the handle is provided to facilitate the user to open the oven door.

Citation Information

Patent Citations

  • Matt frit for building ceramic and preparation method for matt frit for building ceramic

    CN102557739A